The golden egg [compact disc, unabridged] - Leon, Donna (Leon, Donna. Commissario Guido Brunetti mystery., 2013)
The mentally handicapped man who worked at Brunetti's dry cleaners has just died of an overdose, and Brunetti's wife Paola loathes the idea that he lived and died without anyone noticing or helping him. To please his wife, Brunetti investigates the death, and is surprised to find nothing on the man: no birth certificate, no passport, nothing. As secrets unravel, Brunetti suspects an aristocratic family might be connected. But why would anyone want this sweet, simple-minded man dead?